FORMULASI GRANUL EFFERVESCENT SARI BUAH PALA (Myristica fragrans H.) - Ribka Mandagi; Gregoria S.S. Djarkasi; Erny Nurali; Lucia Mandey (COCOS, 2015)
ABSTRACTNorth Sulawesi is one of nutmeg producer in Indonesia. Nutmeg can be separated in 4 parts which is flesh, seed, mace and skin. However, nutmeg flesh became a waste because it has a lower selling price than the seed and mace. Therefore it needs to develop to more innovative and creative form like effervescent. Effervescent defined as a form that produced gas bubbles (CO2) as a result of chemical reaction. The reaction of effervescent is between the citric acid and Na-bicarbonate. The aim of this research is to determine some physical, chemical and sensory characteristic in variation of citric acid and na-bicarbonate of nutmeg flesh effervescent formula. The formulas are separated to 4, with the variation concentration of citric acid and Na-bicarbonate. The results of this research show that the variation of citric acid and na-bicarbonate gave a significant differentiation to dissolving time, moisture content, total acid and taste of nutmeg flesh effervescent. Dissolving time is about 1 minutes 36 seconds to 2 minutes 2 seconds. Moisture content is about 7,15% to 8,13%. Total acid is about 0.0031% to 0.0120%. The organoleptic test of nutmeg flesh effervescent gave the result that formula C has the highest score and parallel as almost delight.